Lipocalin-2 in preoperative cerebrospinal fluid is a biomarker for postoperative delirium after hip fracture surgery in older adults: a prospective cohort study - Kang, Ning; Han, Xiaoguang; Liu, Taotao; Huang, Jie; Li, Zhuzhu; Li, Zhengqian; Yuan, Yi; Song, Yanan; Yang, Ning; Guo, Xiangyang (Frontiers in Neurology, 2025)
BackgroundPostoperative delirium (POD) is a common central nervous system complication in older adult surgical patients. At present, the mechanism for POD is still unclear. Lipocalin-2 (LCN2) may have an impact on cognitive function, but the relationship between LCN2 and POD has remained unclear. Therefore, we sought to investigate the relationship between the levels of LCN2 in plasma and cerebrospinal fluid (CSF) and the occurrence of POD in older adults undergoing hip fracture surgery.MethodsWe conducted a prospective observational cohort study involving 186 older adults (≥65 years old) who underwent hip fracture surgery under spinal anesthesia. CSF and blood samples were collected. The levels of LCN2, interleukin-6 (IL-6), and interleukin-1 (IL-1) were measured using an enzyme-linked immunosorbent assay (ELISA). We used the 3-min diagnostic interview to evaluate delirium defined by the Confusion Assessment Method (3D-CAM), to screen for POD, and the Memorial Delirium Assessment Scale (MDAS) to evaluate the severity of delirium. Multivariable logistic regression was applied to identify independent predictive factors for POD. The relationship between CSF LCN2 levels and POD risk was assessed through receiver operating characteristic (ROC) curve analysis. Correlation analysis was used to investigate the association between CSF LCN2 and MDAS scores as well as IL-6.ResultsAmong the 186 patients ultimately included, 29 (15.6%) developed POD. Their preoperative CSF LCN2 level was significantly higher than that of those without POD (p = 0.001). The multivariable logistic regression analysis revealed that an elevated preoperative CSF LCN2 level [odds ratio (OR) 2.546, 95% confidence interval (CI) 1.345–4.822; p = 0.004] was an independent predictor of POD. Moreover, among POD group patients, preoperative CSF LCN2 levels were positively correlated with the MDAS scores (r = 0.688, p < 0.001) and CSF IL-6 levels (r = 0.379, p = 0.043). ROC analysis of preoperative CSF LCN2 showed an area under the curve of 0.713 (95% CI 0.615–0.810) with a specificity of 75.0%, and sensitivity of 58.6%.ConclusionElevated preoperative CSF LCN2 levels are associated with an increased risk and severity of POD in older adults undergoing hip fracture surgery.Clinical trial registrationhttps://www.chictr.org.cn/, ChiCTR2200061407.